A reappraisal of Katona's adaptive theory of consumer behaviour using U.K. data. (14th January 2022) - Gausden, Robert; Hasan, Mohammad
Abstract: The objective of this paper is to conduct a reappraisal of Katona's (1968) adaptive theory of consumer behaviour, which maintains that discretionary consumption is partly determined by attitudes and expectations of households. Initially, using UK data, we follow Katona by empirically examining whether changes in personal expenditure on durable goods are connected to earlier movements in consumer confidence. Evidence of a lack of a stable relationship between these two variables encourages us to perform a disaggregated analysis involving 111 components of four different forms of consumption, which enables construction of an aggregate measure of discretionary spending. We find that sufficient criteria are satisfied for the sentiment index to be accepted as a reliable predictor of the growth of gratuitous expenditure. In conclusion, then, it would seem that the validity of Katona's theory can be revived if we are prepared to discard the assumption that durable goods' consumption is synonymous with discretionary spending.